Advance in the study of limonene epoxidation with H2O2 catalyzed by Cu(II) complex heteropolytungstates - Egusquiza, María Gabriela (2012)
The complex heteropolyoxotungstates of formula K10[M4(H2O)2(PW9O34)2]·20H2O (PWM) with M= Co(II), Zn(II), Cu(II) and Mn(II), and their precursor, Δ-Na8HPW9O34·19H2O (Δ-PW9), were evaluated as bulk in limonene epoxidation using H2O2 as oxidant, 1,2 dicloroethane as solvent and metiltricaprilamonium chloride (Aliquat 336) as a phase transfer agent at 2 °C. In these biphasic conditions PWCu was the most active phase. Subsequently this phase was supported on γ-Al2O3, the metal load was determined by AAS, ICP and X-ray fluorescence and the preservation of PWCu structure was confirmed by XPS and Raman microprobe. PWCu/γ-Al2O3 was evaluated at 70 °C with acetonitrile as solvent. The pure PWCu showed a higher conversion to epoxide but lower selectivity due to the formation of secondary products